Psychosocial barriers and enablers of exclusive breastfeeding: lived experiences of mothers in low-income townships, North West Province, South Africa - Chantell Witten; Nicole Claasen; Herculina S. Kruger; Anna Coutsoudis; Herman Grobler (BMC, 2020)
Abstract Background Despite national efforts to promote exclusive breastfeeding (EBF), South Africa's EBF rate is only 32 %. The aim of this study was to examine the rate of EBF discontinuation and the lived experiences of breastfeeding mothers at postnatal time points 3-14 days, 4-8 weeks, 10-14 weeks and 20-24 weeks. Methods This community-based mixed-methods study collected data within a prospective cohort study on sociodemographics, the Edinburgh Postnatal Depression Scale (EPDS) and the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) at 6-8 weeks with infant feeding data collected at 4-8, 10-14 and 20-24 weeks from 159 mothers living in low income areas. Six focus groups with 32 mothers with infants aged 6-24 weeks were conducted. Descriptive statistics was used for the quantitative data and thematic analysis for qualitative data. Results The majority of mothers were unmarried (84.9%), living with family (69.2%) and unemployed (74.2%). Exclusive breastfeeding decreased from 34% at 4-8 weeks to 9.7% at 20-24 weeks. Mixed feeding with infant formula increased from 17.0 to 30.6% and food feeding from 3.1 to 54.2%. While there were no statistically significant associations between EBF and any of the quantitative sociodemographic variables, in the qualitative data, codes associated with barriers were more than enablers. The themes were Mothers' attributes (wellbeing, experiences and relationships) with the code mother's stress the strongest barrier, Mother's knowledge, attitudes and practices of breastfeeding with the code conventional medicines the strongest barrier, Family environment with the code home setting the strongest barrier, Social environment with public spaces and places a barrier and in Baby cues the code baby stomach ailments the barrier. Within these same themes mother's positive emotions, benefits of breastfeeding, support in the home, access to information and services from health professionals and baby's health were strong enabling factors. Conclusions Low EBF, high mixed feeding and a high EPDS score were explained by the barriers identified in the qualitative data. The data suggests that mothers from low-income households would be better supported through interventions that address food insecurity; family relationships and those that build confidence in mothers and resilience in confronting difficult and hostile breastfeeding environments.